Assessment of a non-invasive haemoglobin sensor NBM 200 among pregnant women in rural India - Ahankari, Anand S.; Fogarty, Andrew W.; Tata, Laila J.; Dixit, J.V.; Myles, Puja R. (BMJ Publishing Group, 2016)
Objective: This study aimed to assess a non-invasive haemoglobin sensor NBM 200 in pregnant women in a rural Indian setting. Methods: The study population consisted of women between 3 to 5 months of pregnancy, from 33 villages in Tuljapur and Lohara blocks of Osmanabad district, Maharashtra between April 2014 and June 2015. Haemoglobin (Hb) measurements obtained from the non-invasive sensor NBM 200 were compared with measurements obtained from an automated haematology analyser Sysmex XP-100, using the Bland Altman method and Spearman’s Rank correlation coefficient. Interclass correlation coefficient (ICC), sensitivity and specificity values were used to assess the anaemia diagnostic accuracy of NBM 200 against the gold standard (Sysmex XP-100). Results: Data were obtained from 269 pregnant women (median age: 21 years, Interquartile range: 19 to 23 years). Haemoglobin levels estimated by the Sysmex XP-100 analyser ranged from 5.5 g/dL to 14.1 g/dL (mean: 10.0 g/dL, standard deviation (SD): 1.28), while measurements obtained from NBM 200 ranged from 9.5 g/dL to 14.6 g/dL (mean: 11.9 g/dL, SD: 1.43). The Spearman’s test found a significant, moderately positive correlation between the two methods (rs= 0.4, p<0.001), ICC was 0.22, and the Bland-Altman analysis showed a mean difference of -1.8 g/dL (95% Confidence interval (CI): -2.06 to -1.71) indicating a systematic overestimation of Hb using the NBM 200. The NBM 200 showed low sensitivity (33.7%; 95% CI: 27.3 - 40.5) but high specificity (91.8%; 95% CI: 81.9 - 97.3) for the diagnosis of anaemia. Conclusion: Haemoglobin measurements obtained from the NBM 200 were higher with consequent underestimation of anaemia as compared with the gold standard reference method. This limits the use of the NBM 200 as an anaemia diagnostic test in our study population consisting of women during pregnancy.